Sustaining Traditional Ethnomedicinal Knowledge and Protected Areas in Synergy: A Case Study of Overa-Aru Wildlife Sanctuary in Kashmir Himalaya - Islam, Tajamul; Nawchoo, Irshad A.; Magray, Junaid A.; Khuroo, Anzar Ahmad (Planta Medica, 2023)
The ethnic communities living near protected areas are critically dependent on medicinal plants for their healthcare. Although several ethnomedicinal studies are available from the Himalaya, quantitative studies focusing on protected areas in this region are largely overlooked. In this study, we aimed to document the ethnomedicinal plants of the Overa-Aru wildlife sanctuary in Kashmir Himalaya. We conducted a systematic field survey in the study area during 2020 – 2021 to collect primary data from 110 participants through semi-structured interviews and questionnaires. The data was analyzed using quantitative indices and Pearsonʼs correlation. We recorded 64 plant species used against 8 human disease categories, including some first-time reports from the region. Asteraceae and Lamiaceae were the most dominant families and herbs were the dominant growth form. The most common plant part used were leaves, and the main method of preparation was decoction. Plant species with the highest relative frequency of citation was Achillea millifolium (0.83). Informant consensus factor for each disease category ranged from 0.94 to 0.97. We found a strong positive correlation between participantsʼ age and citations (r = 0.85), but a negative correlation between the participantsʼ education status and citations (r = − 0.11). Our results revealed that the younger generation possesses the least ethnomedicinal information. We recommend that the species with high use values and fidelity level merit priority in phytochemical and pharmaceutical studies. Our findings highlight that protected areas, besides their prime importance in biodiversity conservation, play a pivotal role in providing the healthcare provisioning ecosystem services to the ethnic communities.
Keywords: Himalaya; human diseases; medicinal plants; protected area; quantitative analysis; traditional knowledge